(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effect of work discipline and leadership style on the performance of employees of PT. Suraco Jaya Abadi Motor Palopo. This study consists of 3 variables, namely work discipline (X1), leadership style (X2), and Performance (Y). This research method uses the method of observation or direct observation and questionnaires. The population of this study was all employees of PT. Suraco Jaya Abadi Motor Palopo, numbering 40 people. All populations are sampled (census). The questionnaire was used as a primary data collection tool. Data analysis used multiple correlations with the help of SPSS. The results of this study indicate that work discipline and leadership style have a positive and significant influence on employee performance.